2013
DOI: 10.1186/1559-4106-8-17
|View full text |Cite
|
Sign up to set email alerts
|

ToF-SIMS analysis of osteoblast-like cells and their mineralized extracellular matrix on strontium enriched bone cements

Abstract: Commonly used implants for therapeutic approaches of non-systemically impaired bone do not sufficiently support the healing process of osteoporotic bone. Since strontium (II) has been proven as an effective anti-osteoporotic drug new types of strontium enriched calcium phosphate bone cements were developed. As osteoporosis is characterized by an imbalance of osteoblast and osteoclast activity the influence of this newly generated strontium enriched biomaterials on the cellular behavior of osteoblast-like cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 37 publications
0
34
0
Order By: Relevance
“…51 Thormann et al 16 showed higher Sr concentrations in zones of increased bone formation, supporting this finding. More studies on the relationship between Sr concentrations and bone formation are needed to clarify this theory.…”
Section: Discussionmentioning
confidence: 73%
“…51 Thormann et al 16 showed higher Sr concentrations in zones of increased bone formation, supporting this finding. More studies on the relationship between Sr concentrations and bone formation are needed to clarify this theory.…”
Section: Discussionmentioning
confidence: 73%
“…[23][24][25][26][27] Strontium that is incorporated into bone cements has been found to improve bone formation and reduce bone resorption in vivo. 28 Sabareeswaran et al investigated the bioactive fixation of strontium-containing glass ceramics and found out that it led to osseointegration during shortterm implementation. 29 Schumacher et al investigated the effect of strontium(II) released from calcium phosphate bone cement on primary human mesenchymal stem cells and reported that it could be useful for local therapy, particularly in osteoporotic bone.…”
Section: Discussionmentioning
confidence: 99%
“…A 2 keV oxygen etching beam was also used recently to perform 3D ToF-SIMS imaging to investigate the uptake of strontium from bone cements by osteoblast like cells. 36 In this study the oxygen beam was selected due to the increased ionization efficiency of the strontium ions despite the increased damage to molecular species compared with C 60 þ .…”
Section: Biological Samplesmentioning
confidence: 99%